2013
DOI: 10.1177/1938640013514271
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Acute Extensor Hallucis Longus Tendon Injuries

Abstract: Primary repair or reconstruction of EHL tendon lacerations is a reliable procedure that restores hallux alignment and function in most patients as measured by the validated FAAM questionnaire. Deep tendon transfer from the extensor digitorum longus may be performed if EHL tendon edges are not opposable thus eliminating the need for allograft reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 10 publications
1
29
0
1
Order By: Relevance
“…Methods to reconstruct the tendons of the foot and ankle, similar to the cases presented here, have been published. One group described repairing damaged tendons in the foot according to a two‐step algorithm; primary repair is preferred, whereas large or otherwise complex tendinous defects require tendon transfer (Wong, Daniel, & Raikin, ). Another author explored the use of the extensor hallucis brevis tendon as a donor for defects in EHL (Berens, ).…”
Section: Discussionmentioning
confidence: 99%
“…Methods to reconstruct the tendons of the foot and ankle, similar to the cases presented here, have been published. One group described repairing damaged tendons in the foot according to a two‐step algorithm; primary repair is preferred, whereas large or otherwise complex tendinous defects require tendon transfer (Wong, Daniel, & Raikin, ). Another author explored the use of the extensor hallucis brevis tendon as a donor for defects in EHL (Berens, ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite more robust data describing acute EHL injuries, very few reports have addressed neglected EHL tendon ruptures with severe retraction. In cases in which tendon retraction persists after tendon mobilization, or in chronic conditions (≥6 weeks) in which the tendon ends cannot be reapproximated or the tendon ends have become severely degenerated, a tendon graft is the procedure of choice (5,7). Case studies have suggested the use of split EHL tendon lengthening (8), a fascia lata allograft (9), a gracilis autograft (13), and an extensor digitorum longus free tendon graft (16) for such repair.…”
Section: Discussionmentioning
confidence: 99%
“…Early recommendations for EHL tendon ruptures and lacerations suggested that these injuries could be treated without operative repair (2,3). However, more recent reports have described improved hallux function after EHL repair with tendon transfer, tendon lengthening, and tendon grafting (4)(5)(6)(7)(8)(9). In general, a trend has occurred toward primary surgical repair of acute tendon injuries or surgical reconstruction if tendon retraction prevents tension-free tendon opposition (1,4,9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At latest follow-up, 12 months postoperatively, the patient showed an F I G U R E 1 After the excision of a myxoinflammatory fibroblastic sarcoma recurrence, the EHL tendon was sacrificed, leaving a 14 × 5 cm soft-tissue defect and 14-cm tendon gap. EHL, extensor hallucis longus F I G U R E 2 A 14 × 5 cm radial forearm flap with a 16-cm section of palmaris longus tendon including the investing deep fascia was harvested from the left forearm on a vascular pedicle It has been estimated that the EHL muscle contributes 15% of the dorsiflexion strength of the ankle, and injury or surgical excision of EHL tendon without reconstruction cause hallux dysfunction and results in a flexion deformity at interphalangeal joint (Bastías et al, 2019;Griffiths, 1965;Joseph & Barhorst, 2012;Kessler, 1973;Lipscomb & Kelly, 1955;Park et al, 2003;Pedreira et al, 2019;Robertson, Nutton, & Keating, 2006;Smith & Coughlin, 2008;Soucacos et al, 1992;Taylor & Townsend, 1979;Thordarson & Shean, 2005;Wong et al, 2014;Zielaskowski & Pontious, 2002). There is no consensus in the literature regarding the ideal reconstruction of EHL tendon after oncologic resection: most of the cases reported reconstructions of acute or chronic tendon rupture.…”
Section: Case Reportmentioning
confidence: 99%